Intramodal Olfactory Priming of Positive and Negative Odors in Humans Using Respiration-Triggered Olfactory Stimulation (RETROS) - Hoffmann-Hensel, Sonja Maria; Freiherr, Jessica (Chemical Senses, 2016)
Priming describes the principle of modified stimulus perception that occurs due to a previously presented stimulus. Although we have begun to understand the mechanisms of crossmodal priming, the concept of intramodal olfactory priming remains relatively unexplored. Therefore, we applied positive and negative odors using respiration-triggered olfactory stimulation (RETROS), enabling us to record the skin conductance response (SCR) and breathing data without a crossmodal cueing error and measure reaction times (RTs) for olfactory tasks. RT, SCR, and breathing data revealed that negative odors were perceived significantly more arousing than positive ones. In a second experiment, 2 odors were applied during consecutive respirations. Here, we observed intramodal olfactory priming effects: A negative odor preceded by a positive odor was rated as more pleasant than when the same odor was preceded by a negative odor. Additionally, a longer identification RT was found for the second compared with the first odor. We interpret this as increased "perceptual load" due to incomplete first odor processing while the second odor was presented. Furthermore, intramodal priming can be considered a possible reason for the increase of identification RT. The use of RETROS led to these novel insights into olfactory processing beyond crossmodal interaction by providing a noncued unimodal olfactory test, and therefore, RETROS can be used in the experimental design of future olfactory studies.
Keywords: intramodal priming; olfaction; respiration; skin conductance response